2020
DOI: 10.3390/plants9121702
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Breeding Philosophy of Wheat to Fusarium Head Blight (FHB): Resistance Components, QTL Identification, and Phenotyping—A Review

Abstract: Fusarium head blight has posed continuous risks to wheat production worldwide due to its effects on yield, and the fungus provides additional risks with production of toxins. Plant resistance is thought to be the most powerful method. The host plant resistance is complex, Types I–V were reported. From the time of spraying inoculation (Type I), all resistance types can be identified and used to determine the total resistance. Type II resistance (at point inoculation) describes the spread of head blight from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 92 publications
(177 reference statements)
0
63
1
2
Order By: Relevance
“…Practical identification of varieties with greater and lower levels of resistance to FHB followed shortly after the different types of resistance were recognized [ 241 ]. Resistance is quantitative in nature and QTLs for resistance have been localized to all wheat chromosomes [ 29 ]. Although a series of seven major QTLs ( fhb1–7 ) have been identified and mapped, none of them provide complete resistance and their mode of action is not well understood even if the protein they encode is known.…”
Section: Pre-harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical identification of varieties with greater and lower levels of resistance to FHB followed shortly after the different types of resistance were recognized [ 241 ]. Resistance is quantitative in nature and QTLs for resistance have been localized to all wheat chromosomes [ 29 ]. Although a series of seven major QTLs ( fhb1–7 ) have been identified and mapped, none of them provide complete resistance and their mode of action is not well understood even if the protein they encode is known.…”
Section: Pre-harvestmentioning
confidence: 99%
“…The amount of toxin contamination can be considerable, but is not necessarily directly related to the severity of the disease outbreak. Disease resistance of wheat to different Fusarium species is governed by species-non-specific QTLs [ 27 , 28 , 29 ]. Most lines have no more than moderate resistance to FHB.…”
Section: Introductionmentioning
confidence: 99%
“…Typical R genes such as NBS-LRR, receptor like proteins (RLP) and receptor like kinases (RLK) have been cloned since their phenotypes can be easily observed ( Dangl and Jones, 2001 ). For some diseases such as sclerotinia diseases in rapeseed, sunflower and soybean and fusarium head blight in cereal crops, no vertical, qualitative or race-specific resistance has been identified so no typical R genes for these diseases has been cloned ( Behla et al, 2017 ; Mesterhazy, 2020 ). In this study, the horizontal resistance of BLMR2 has been stressed since it conferred intermediate resistance under field conditions ( Dandena et al, 2019 ) and showed intermediate resistance to all isolated tested under controlled environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms can be mixed with maturation, especially with crops such as oats, and the disease can be quite unevenly spread in fields because it may spread from infested seeds or overwintered crop residue. Plant breeders must therefore rely on inoculated disease nurseries to get evenly distributed infections, and they also need to include analyses made for grain samples [95] to screen resistance to FHB. These analyses, such as the determination of mycotoxin content by enzyme-linked immunosorbent assays (ELISA), are expensive, and alternative methods like NIR spectroscopy are being considered for analysing the yield samples or for making field phenotyping more reliable by chlorophyll fluorescence [96] or hyperspectral sensors [97], and RGB [98].…”
Section: Differences With Other Uav Imaging Applicationsmentioning
confidence: 99%